Assessment of antiplatelet therapy response in pediatric patients following cardiac surgery by microfluidic assay. (March 2020) - Kapileshwarkar, Yamini; Gelmini, Lucas; Tseng, Yu-Shan; Jackson, Tannoa; Gao, Xiufeng; Richards, Kristen; Dokas, Michelle; Walters, Henry; Hines, Patrick C.
Abstract: Introduction: Anti-platelet therapies, like aspirin, are routinely used following many surgical repairs for congenital heart disease to prevent life-threatening thrombotic complications. Optimal dosing is not well studied and determination of real-time dose response to prophylactic aspirin is not routinely performed due to blood volume requirements and poor predictive value of existing platelet function assays (PFAs). Our objective was to study platelet function and thrombosis in post-operative cardiac patients under physiologic shear conditions using a novel collagen-coated microfluidic thrombosis assay (MTA) compared to a standard whole blood aggregometry (WBA) assay before and after clinically and experimentally administered aspirin therapy. Methods: We recruited congenital heart surgical patients with post-operative indications for aspirin therapy at the Children's Hospital of Michigan. Samples of 1.8 mL blood were drawn within 24 h of initiating aspirin (D0 ) and 24 to 48 h after initiating aspirin (D1 ). Blood samples were split for use in the MTA and the WBA. The MTA sample was run through collagen coated microfluidic channels at shear stress of 10 dyne/cm2 and pulse frequency of 1.67 Hz to simulate physiologic flow conditions. Each sample was run under untreated conditions (reflects the study subject's endogenous platelet function, D0, D1 ) and following exogenous aspirin administration (reflects maximum theoretical platelet response to aspirin, +eASA). The kinetics of thrombus formation was assessed as area percent of signal intensity (total fluorescent intensity, TFI) of thrombosis at 6 &10 min and as area under curve (AUC) for MTA and as AUC and impedance at 6 min for WBA. Results: Results from MTA and WBA on pre- and post-aspirin blood samples collected from 18 subjects, with and without exogenously added aspirin, were analyzed in this study. Fold changes for AUC were calculated for each test and were compared using Wilcoxon signed rank test; this showed no statistically significant difference. Three of the patients were found to have no response to endogenous or exogenous aspirin. Conclusions: We observed that measured platelet function is variable and potential sources of variability could be sample source, timing of sample from bypass, platelet count, transfusions and others. Standard aspirin doses might not be adequate for patients who are at high risk of thrombosis. In this study, we demonstrate the feasibility of employing microfluidic thrombosis assay to assess real time clinical platelet function in the cardiac ICU setting. Microfluidic assays provide real time assessment of platelet function under physiologic flow conditions and might be helpful with optimizing aspirin doses. Further studies on larger cohorts are required to validate this possibility. Highlights: MTA can be useful in assessing real-time clinical platelet function and aspirin responsiveness in post-op cardiac patients. Use of microfluidic assay can be used to titrate aspirin for optimal antiplatelet response. Rotation shear seen with WBA may be inferior in activating platelet function compared to linear shear in microfluidic assay.